2021
DOI: 10.1080/15569527.2021.1902342
|View full text |Cite
|
Sign up to set email alerts
|

Efficient agent degradation within skin is important for decontamination of percutaneously exposed VX

Abstract: Aim of the study: Following percutaneous exposure to the nerve agent VX, the remaining intact agent within the skin after decontamination is of great concern. Consequently, this leads to prolonged agent release to the blood circulation resulting in sustained intoxication, which may complicate the medical management. The decontamination procedure used should therefore possess the ability for agent removal both on and within the skin. The efficacy of three decontamination procedures was evaluated by measuring VX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 50 publications
(76 reference statements)
3
7
0
Order By: Relevance
“…While most studies occurred at room temperature (approximately 25°C), Thors et al ( 2021a ) also conducted soapy water decontamination at −5°C and −15°C. While the cumulative penetration of VX significantly increased (66.5 ± 5.5 μg/cm 2 compared to no-decontamination control of 24.6 ± 6.6 μg/cm 2 ) following wet decontamination at room temperature as previously identified (Thors et al 2021b , 2020 ), there was no significant alteration at either −5°C (36.0 ± 3.7 μg/cm 2 compared to 28.9 ± 8.9 μg/cm 2 ) or −15°C (35.8 ± 9.4 μg/cm 2 ompared to 34.4 ± 5.3 μg/cm 2 ). Skin penetration of VX was significantly reduced at lower temperatures when compared to room temperature, although this is based upon cumulative dose over 5 hr, and presence of any temporal phenomenon is not mentioned within the study.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…While most studies occurred at room temperature (approximately 25°C), Thors et al ( 2021a ) also conducted soapy water decontamination at −5°C and −15°C. While the cumulative penetration of VX significantly increased (66.5 ± 5.5 μg/cm 2 compared to no-decontamination control of 24.6 ± 6.6 μg/cm 2 ) following wet decontamination at room temperature as previously identified (Thors et al 2021b , 2020 ), there was no significant alteration at either −5°C (36.0 ± 3.7 μg/cm 2 compared to 28.9 ± 8.9 μg/cm 2 ) or −15°C (35.8 ± 9.4 μg/cm 2 ompared to 34.4 ± 5.3 μg/cm 2 ). Skin penetration of VX was significantly reduced at lower temperatures when compared to room temperature, although this is based upon cumulative dose over 5 hr, and presence of any temporal phenomenon is not mentioned within the study.…”
Section: Discussionsupporting
confidence: 78%
“…Skin penetration of VX was significantly reduced at lower temperatures when compared to room temperature, although this is based upon cumulative dose over 5 hr, and presence of any temporal phenomenon is not mentioned within the study. Thors et al ( 2020 ); (2021b) ) suggested that the lack of wash-in effect at lower temperatures may be due to freezing of water on the surface of the skin (despite the skin being held at 32°C) and that cold soapy water reaching into the skin may have delayed further VX penetration within the skin. While this is an important consideration for incidents that occur at sub-zero temperatures, the design of decontamination interventions at low ambient temperatures requires redesign to prevent hypothermia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cause for lowered VX skin penetration following soapy water decontamination in cold air temperature could in future studies should be evaluated by using skin stripping methodology or similar techniques to determine the agent amounts in different skin layers (Thors et al, 2021). Although the low air temperature beneficially influenced the efficacy of soapy water decontamination, cold water on skin is also a potential cause for environmental injuries such as hypothermia (Cheshire, 2016).…”
Section: Discussionmentioning
confidence: 99%